Gold, Silver, and Palladium Nanoparticles: A Chemical Tool for Biomedical Applications - Yaqoob, Sundas Bahar; Adnan, Rohana; Rameez Khan, Raja Muhammad; Rashid, Mohammad (Frontiers in Chemistry, 2020)
Herein, the role of metal-based nanoparticles (NPs) in biomedical analysis and the treatment of critical deceases been highlighted. In the world of nanotechnology, noble elements such as the gold/silver/palladium (Au/Ag/Pd) NPs are the most promising emerging trend to design bioengineering materials that could to be employed as modern diagnostic tools and devices to combat serious diseases. NPs are considered a powerful and advanced chemical tool to diagnose and to cure critical ailments such as HIV, cancer, and other types of infectious illnesses. The treatment of cancer is the most significant application of nanotechnology which is based on premature tumor detection and analysis of cancer cells through Nano-devices. The fascinating characteristic properties of NPs—such as high surface area, high surface Plasmon resonance, multi-functionalization, highly stable nature, and easy processing—make them more prolific for nanotechnology. In this review article, the multifunctional roles of Au/Ag/Pd NPs in the field of medical science, the physicochemical toxicity dependent properties, and the interaction mechanism is highlighted. Due to the cytotoxicity of Ag/Au/Pd NPs, the conclusion and future remarks emphasize the need for further research to minimize the toxicity of NPs in the bio-medicinal field.